Astragalin improved mitochondrial function through AMPK/PGC-1α pathway and alleviated renal injury in diabetic nephropathy - Yi Luo; Meng-jing Wang; Shu-fen Liu; Shuang Yuan; Hao Huang (Editorial Department of Journal of Clinical Nephrology, 2024)
Objective To explore the effect and mechanism of astragalin （AG） in alleviating renal injury in diabetic kidney disease(DKD). Methods db/m and db/db mice aged 16 weeks were randomized into four groups of db/m, db/m+AG （5 mg/kg）, db/db and db/db+AG （5 mg/kg）. Primary Human renal cortex proximal convoluted tubule epithelial cells （HK-2） were cultured in vitro and assigned into four groups of control （5 mM glucose）, control +AG （5 mM glucose +10 μM AG）, high glucose （HG, 30 mM） and HG+AG （30 mM glucose +10 μM AG）. Urinary albumin-creatinine ratio, blood glucose （BG） and body weight were detected. The pathological changes of kidney were observed by （periodic acid-Schiff PAS） and MASSON stain. The expressions of adenosine monophosphate-activated protein kinase （AMPK）, phosphorylation （p）-AMPK, peroxisome proliferator-activated receptor γ coactivator 1α （PGC-1α） and antiapoptotic protein B-cell lymphoma-2 （Bcl-2） were determined by Western blot. The expression level of PGC-1α was detected by fluorescent stain. Molecular docking was performed for detecting the binding force of AG and PGC-1α. Results As compared with db/m group, there were no changes in body weight, BG or kidney injury in db/m+AG group. It implied that oral AG had some safety. As compared with db/db group, body weight, BG and urinary albumin creatinine ratio decreased and renal tissue lesions lessened in db/db+AG group （P＜0.01）. As compared with db/db group, p-AMPK/AMPK ratio, PGC-1α protein and Bcl-2 spiked in db/db+AG group （all P＜0.01）. As compared with control group, p-AMPK/AMPK ratio, PGC-1α protein and Bcl-2 declined in HG group （P＜0.001）. As compared with HG group, p-AMPK/AMPK ratio, PGC-1α protein and Bcl-2 jumped in HG+AG group （all P＜0.01）. As compared with db/db group, the expression of PGC-1α protein was up-regulated in db/db+AG group （P＜0.01）. As compared with HG group, the expression of PGC-1α protein rose in HG +AG group （P＜0.01）. In molecular docking, AG could stably conjugate with PGC-1α protein. Conclusion AG improves mitochondrial function and alleviates kidney injury through AMPK/PGC-1α pathway, thereby delaying the progression of DKD.